Learning Style System for Learning Achievement in Equality Education - Erlangga, Erwin; Sugiarti, Rini; Daru, April Firman; Desyantoro, Irwan; Veronika, Nofita (Universitas Negeri Semarang, 2021)
Humanity is currently in deep sadness due to the outbreak of Coronavirus Disease (Covid-19) which has hit almost all parts of the world. Indonesia spontaneously implemented policies of learning from home, working from home, and worshiping at home. One of the learning methods used by the Indonesian education system is online or the abbreviation for the network. Online or online is a learning method that is carried out online. While online courses are courses that are wholly or partly held online or online, using learning management. This study aims to determine the effect of the learning style system on student achievement inequality education. The method used in this research is experimental. The study population numbered 120 students who were selected using a simple random sampling technique. Data collection was carried out by distributing learning style questionnaires and documenting student report cards within 1 semester. This study uses quantitative data analysis techniques, normality and homogeneity tests, and ANOVA tests. Hypothesis testing used a one-way ANOVA test with data processing using Lisrel. The results showed that the learning style had a significant influence or contribution to the learning achievement of students. This can be seen from the results of the significant value of 0.500 so that the significance value of the ANOVA test of students is more than 0.45. Novelty is product style learning system, this is very important for education